2011
DOI: 10.1155/2011/518710
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Enrollment in a Specialized Interdisciplinary Neuropathic Pain Clinic

Abstract: Despite the limitations of performing a real-world, uncontrolled study, patients with NeP benefit from enrollment in a small interdisciplinary clinic. Education and a complete diagnostic evaluation are hypothesized to lead to improvements in anxiety and, subsequently, pain severity. Questions remain regarding the long-term maintenance of these improvements and the optimal structure of specialized pain clinics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 62 publications
0
19
0
1
Order By: Relevance
“…We prospectively evaluated patients with NeP at a tertiary care NeP clinic in Calgary, AB, Canada 36. This investigation was designed as a prospective cohort assessment as part of the patients’ regular clinical care.…”
Section: Methodsmentioning
confidence: 99%
“…We prospectively evaluated patients with NeP at a tertiary care NeP clinic in Calgary, AB, Canada 36. This investigation was designed as a prospective cohort assessment as part of the patients’ regular clinical care.…”
Section: Methodsmentioning
confidence: 99%
“…Regarding the use of QL parameters to evaluate chronic neuropathic pain individuals, the literature is scarce. Other authors refer in their studies that pain intensity has only decreased after one year of follow up, while QL indices and anxiety have improved after 6 months 15 . They concluded that educational activities and thorough interdisciplinary evaluation lead to better QL, thus confirming our study.…”
Section: Discussionmentioning
confidence: 96%
“…One obvious parameter could be the change in waiting list time for pain clinics, although this might not necessarily reflect on the quality of care given in the community. We recommend the following parameters that would give evidence of a change in the bio-psycho-social aspects of the chronic pain phenomena: 1) in the biological aspect we could follow such parameters as VAS and the use of pain medication 28 , 29 ; 2) on the psychological aspect one could examine quality of life measures such as patient satisfaction, stress, anxiety, and anger 30 , 31 ; and 3) such social parameters as days off work and physician visitation rates. …”
Section: Practical Implicationsmentioning
confidence: 99%